No Exit: Ten Years of "Privacy vs. Speech" Post-Sorrell - G.S. Hans (Washington University Journal of Law & Policy, 2021)
Privacy and free speech are often described as oppositional forces. This Essay analyzes First Amendment jurisprudence emphasizing the ten years after Sorrell vs. IMS Health was decided in 2011. In this Essay, Hans contextualizes First Amendment challenges to privacy laws. Hans cautions that the Supreme Court has moved perilously close towards a jurisprudence under which privacy laws are nearly impossible to craft. Hans demonstrates that the need for privacy regulation can satisfy a strict scrutiny standard of review. Hans argues that the stakes for privacy are incredibly high and warrant careful consideration by the Supreme Court.
Keywords: privacy regulation; privacy; free speech; First Amendment; strict scrutiny; jurisprudence; Sorrell vs. IMS Health; Supreme Court; Supreme Court of the United States; SCOTUS